‘Grace Gets Angry’, or the ‘Tactics’ of Forgiveness: the Biopolitics of Reconciliation in the Postcolony - Barnard-Naudé, Jaco (Oñati Socio-Legal Series, 2017)
This article reconsiders the role of forgiveness in the South African Truth and Reconciliation Commission (TRC). Following the preface, the article situates forgiveness within the Lacanian psychoanalytic registers of real, symbolic and imaginary. These dimensions of forgiveness are presented in dialogical style in order to reflect the spirit of dialogue and voice in accordance with which the TRC took place. Part 6 takes up the discursive problematic of forgiveness and submits it to the genealogy of the TRC as produced by Adam Sitze (2013). Drawing on Sitze, I offer a novel understanding of forgiveness, namely as a Foucaultian norm integral to a biopolitical imperative (here, the imperative of peace). In the concluding parts, I return to the psychoanalytic paradigm in order to consider whether we can nevertheless recognise a certain ‘surplus’ forgiveness in and around the TRC. Whether this may be the case in spite, or because of, the biopolitical deployment of forgiveness, remains an open question.